Increase Interests and Writing Poetry Skills (Meningkatkan Minat dan Kemampuan Menulis Puisi) - Erni Rahayu; Muhammad Rohmadi; Andayani Andayani (Jurusan Tadris Bahasa Indonesia, 2018)
This study aims to improve: 1) student interest in writing poetry and; 2) the ability to write poetry students of class VIII SMP. This research is a classroom action research. The research was conducted in class VIII in one of the junior high schools in Sukoharjo, from August to November 2016. The data sources used were field documents and notes from observational observation. Data analysis techniques with observation, in-depth interviews, tests or assignments and document analysis. Data validity with triangulation of data sources, method triangulation, and informant review. The result of the research concluded that: 1) there is an increase of students 'interest in writing poetry, from 24 students or 47% increase to 24 students or 75%; 2) there is improvement of students' poetry writing skill in learning, from 26 students (81%) to 31 students (96%).Â Penelitian ini bertujuan untuk meningkatkan: 1) minat dan; 2) kemampuan menulis puisi siswa kelas VIII SMP. Penelitian ini merupakan penelitian tindakan kelas. Penelitian dilaksanakan di kelas VIII di salah satu SMP di Sukoharjo, pada bulan Agustus sampai bulan November 2016. Sumber data yang digunakan adalah dokumen dan catatan lapangan dari hasil observasi peneliti. Teknik analisis data dengan observasi, wawancara mendalam, tes atau pemberian tugas dan analisis dokumen. Validitas data dengan triangulasi sumber data, triangulasi metode, dan review informan. Hasil penelitian disimpulkan bahwa: 1) terdapat peningkatan minat siswa dalam menulis puisi, dari 24 siswa atau 47% meningkat menjadi 24 siswa atau 75%, 2) terdapat peningkatan kemampuan menulis puisi siswa dalam pembelajaran, dari 26 siswa (81%) menjadi 31 siswa ( 96%).